The application of the organizational learning perspective in explaining the government's internal auditor’s role development - Wisdana, Monika Yustia; Winardi, Rijadh Djatu; Halim, Abdul; Frendy (Badan Pemeriksa Keuangan Republik Indonesia, 2024)
The management of mineral and coal non-tax state revenue (PNBP Minerba) requires urgent attention and improvement, which can be achieved through appropriate oversight of internal auditors. This study assesses the efficacy of internal audit role development through an organizational learning perspective. Authors interviewed eleven informants from internal auditors of the inspectorate and auditees from the Ministry of Energy and Mineral Resources (KESDM) of the Republic of Indonesia. The data corroborates our theoretical framework within organizational significance theory, which states that the interconnection of the relationship between internal auditors and auditees, the internal audit process, and internal auditor resources culminates in the